Methodologies for pharmacokinetic post-contrastographic dynamic contrast enhancement. (26th April 2010) - Di Paola, L.; Fasano, A.; Russo, V.; Setola, R.
Post-contrastographic dynamic contrast enhancement (DCE) technique is a non-invasive method aimed at inquiring the vascularisation induced by lesions; it relies on the analysis of the perfusion's dynamics of contrast agent (CA) within body tissue. The images derived from magnetic resonance (MR), computer tomography (CT) or ultrasound (US) assessments are analysed to derive a contrast enhancement curve, from which some parameters, useful for diagnosis, are acquired. This approach is only qualitative and the estimated parameters have a poor precision and a scarce physical meaning. To overcome these drawbacks, pharmacokinetic models have been introduced for quantitative DCE analysis. In this work, a pharmacokinetic model is proposed, based on physical parameters; it has been applied to the study of post-contrastographic DCE images and parameter estimation has been performed through a maximum likelihood procedure. Results show anomalous value of blood vessel permeability for ill tissues, when compared to healthy ones.